The Impact of Colonializm on the Spread of English in Modern India - Hidayat, Aufi Saskia Hanny; Aziz, M Syahrul; Al Kayyis, Muhammad Ulin Nuha (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
British colonialism in India at that time certainly had a lot of impact on the Indian state, one of which was in the field of language, namely English which became the second official language after Hindi. This article aims to explain how English also contributed to British colonization in India in many ways. The methods used in this research article will focus on how English affected the social structure, education, communication in Indian society both during the colonial and post-colonial periods. In addition, this article aims to provide a deeper understanding of how English was not only a tool of communication, but also a tool of domination and control in British colonialism in India. Thus English in India is not just a legacy left over from the colonial era but also a tool of social movement and progress in this modern era. <fieldset id="contributors"> Aufi Saskia Hanny Hidayat, Muhammad Syahrul Aziz, Muhammad Ulin Nuha Al Kayyis </fieldset>